Enhanced small neutral but not branched chain amino acid transport after epigenetic sodium coupled neutral amino acid transporter‐2 (SNAT2) cDNA expression in myoblasts. Issue 3 (13th May 2021) - Pearson, Timothy; Wendowski, Oskar; Powell, Penny P.
Abstract: Background: Skeletal muscle mass and function are partly maintained by the supply of amino acids, altered amino acid transport is an important cause of frailty that can lead to decreased independence with increasing age and slow trauma recovery. The system‐A sodium coupled neutral amino acid transporter (SNAT)‐2 coded by gene family SLC38A2 generates a 506 amino acid 56 kDa protein that is an important transporter of amino acids in skeletal muscle. Ageing is associated with a decrease in expression of SNAT2 transporters. Methods: In this study, we used the C2C12 cell line, using myoblast cells and cells differentiated into myotubes. We investigated if the expression of SNAT2 DNA would enhance intracellular amino acid levels and increase their availability for protein synthesis. Results: In control myoblasts and myotubes, we found significantly decreased expression of SNAT2 (6.5× decrease, n  = 4 per group, P  < 0.05) in myotubes than found in myoblasts. After transfection with a SNAT2‐eGFP cDNA plasmid, C2C12 myoblasts significantly increased perinuclear punctate SNAT2‐eGFP expression that persisted and was more cytoplasmic after differentiation into myotubes. Interestingly, transfected cells were significantly more responsive to the hormone 5α‐dihydrotestosterone (DHT, 4.5 nM, by 1.6×, n  = 3 per group, P  < 0.04). Starvation significantly enhanced the amino acid C 14 ‐MeAIB transport (1.7×, n  = 3 per group, P  < 0.05) indicating increased function of SNAT2. Inhibiting SNAT2 with high concentrations of MeAIB (3.3 or 5 mM) significantly reduced C 14 ‐Isoleucine transport by L‐type amino acid transporter (LAT2, 52.8% and 77%, respectively, n  = 3 per group, P  < 0.05). However, there was no increase in the LAT2 transport of C 14 ‐isoleucine detectable in SNAT2‐eGFP transfected cells after DHT (4.5 nM) exposure. This indicated that small amino acid availability was not rate limiting to LAT2 function in myoblasts. Conclusions: Overall, these data show that transfection of SNAT2‐eGFP expression enhanced its function following starvation and treatment with physiological levels of DHT. Enhanced SNAT2 expression in muscle cells offers a viable epigenetic target in pathological conditions associated with altered amino acid transport.